Historisches Sujet und aktuelle Bezüge. Zu Bertolt Brechts Erzählung „Die Trophäen des Lukullus“ (1939) - Ignasiak, Detlef (Studia Germanica Posnaniensia, 2018)
Stories of Bertolt Brecht written at the end of the 30's deal with, among other things the problems of an intellectual who emigrated. It also concerns the story "Trophies of Lucculus" (1939). The Location of the meeting of Lucretius and Lucculus, after the former has already completed his conquests made it possible for the author to confront the character of wars of conquest with the vision-dream wish of peace, reconciliation of the fighting parties. The story contains also references to the contemporary (Munich 1938) situation just before the outbreak of the Second World War; the actual waiting of political parties in Rome (in connection with Lucculus's attitude after his return from a victorious expedition which was difficult to predict) brings associations with the attitude of governments of a number of European states towards the Third Reich. The story is based in fact, on the checked facts (sources: Roman historians Theodor Mommsen), however, Brecht introduces everywhere the "fabricated" historical facts where he thinks it is necessary for the problems of the dialectics of "history". "Fabricated" is also the very meeting of Lucretius and Lucculus; a number of verses of the recited poem “On the nature of things” is by Brecht himself.